خطبة أبي طالب في زواج النبي (ﷺ) من خديجة بنت خويلد: دراسة تطبيقية في علم النحو والدلالة: Abu Talib’s Sermon on the Marriage of the Prophet (PBUH) to Khadija Bint Khuwaylid: An Applied Study in Grammar and Semantics (Al-Qamar, 2025)
This article focuses on the study of Arabic grammar in the text of "Abu Talib's speech during the marriage of the Prophet (ﷺ) to Khadijah bint Khuwaylid." Although this speech was delivered before Islam, it embodies noble values and virtues that later became central to Islamic teachings. The study aims to employ grammatical analysis as a tool to understand heritage texts and uncover their profound meanings. It includes an analysis of verbs, nouns, particles, and sentences within the text, highlighting their significance in their religious and social context. The importance of this study lies in showcasing the role of grammar in comprehending rhetorical messages and enhancing a deeper understanding of heritage texts that reflect ethical and human values.
Keywords: Abu Talib’s Sermon, Marriage of the Prophet (PBUH), Khadija Bint Khuwaylid